Assessing the Impact of Automated Cataloguing Systems on Cataloguing Efficiency in Academic Libraries in South-West, Nigeria - Sodipe, Oluseun Mobolanle; Bamgbose, Adeoye Augustine; Fajiwe, Olabode Thomas; Mabawonku, Temitope Oluwabunmi; Rafiu, Wasiu Kehinde (Communicate: Journal of Library and Information Science, 2025)
This study assessed the impact of automated cataloguing systems on cataloguing efficiency in academic libraries in South-West, Nigeria. A descriptive survey research design was adopted, with total enumeration sampling capturing 89 cataloguers from 12 academic libraries across federal, state, and private institutions. Data were collected through a self-designed, close-ended questionnaire and analyzed using descriptive statistics and Pearson Product Moment Correlation (PPMC). Findings revealed that the level of automated cataloguing system operation is moderately high, with these systems being operated to a very high extent. However, challenges such as inadequate funding, limited staff skills, resistance to change, unfriendly interfaces, and high acquisition and maintenance costs were identified. The study showed that there was a significant relationship between library automation and cataloguing efficiency in academic libraries in South-West, Nigeria (r = .602**, P < .05); there was a significant relationship between automated cataloguing efficiency and effective service delivery in academic libraries in South-West, Nigeria (r = .761**, P < .05). It was recommended that academic library management provide adequate funding for automated cataloguing systems while developers create more user-friendly and intuitive interfaces to meet the needs of library staff and users.